Correction of a Skeletal Class III Malocclusion with Chin Cap Therapy- A Case Report (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Case with skeletal and dental class III malocclusion is presented. The patient was a seven year-old girl with growth potential, having anterior and posterior cross bite, premature loss of mandibular deciduous molar teeth bilaterly. The patients soft tissue profile was concave.The general treatment included chin cap, palatal expansion and comprehensive edge wise orthodontic therapy. DOI: http://dx.doi.org/10.3329/bjodfo.v1i1.15972 Ban J Orthod & Dentofac Orthop, October 2010; Vol-1, No.1, 13-15